POLA PENYERAPAN KUNING TELUR DAN PERKEMBANGAN ORGANOGENESIS PADA STADIA AWAL LARVA IKAN SENGGARINGAN (Mystus nigriceps) - Taufik Budhi Pramono; Sri Marnani (Berkala Perikanan Terubuk, 2009)
The observation was conducted to study the yolk absorption activity andmorphological development on the initial state of senggaringan (catfish) fishlarvae. Larvae used for this research were from the artificial spawning ofbroodstock, reared in fiber tank. The result showed that newly hatched larvae has3.02 mm ±0.14 total length and 1.1202 mm3 yolk volume. During yolk absorptionperiod, organogenesis development and length added also occurred. Larvaedevelopment occurred after hacthing involved the eye spot (23 hours, 1 minute),mouth opening (25 hours, 21 minutes) and pigmentation (50 hours, 5 minutes),.Organogenesis development and the total length increment improve, following theincrease of yolk absorption rate.